The PI3K-Akt pathway is a multifaceted regulator of the macrophage response to diverse group B Streptococcus isolates - De-Leon-Lopez, Yadira S.; Thompson, Michelle E.; Kean, Jessica J.; Flaherty, Rebecca A. (Frontiers in Cellular and Infection Microbiology, 2023)
Group B Streptococcus (GBS), also known as Streptococcus agalactiae, is a common member of the microbial flora in healthy individuals. However, problems may arise when GBS-colonized mothers become pregnant. GBS may be transferred from a colonized mother to her newborn or developing fetus, which may result in complications such as miscarriage, pre-term birth, meningitis, pneumonia, or sepsis. Macrophages play an especially important role in the fetal and newborn response to GBS due to the limited development of the adaptive immune system early in life. The goal of this study was to expand what is currently known about how GBS manipulates macrophage cell signaling to evade the immune system and cause disease. To this end, we investigated whether the PI3K-Akt pathway was involved in several key aspects of the macrophage response to GBS. We explored whether certain GBS strains, such as sequence type (ST)-17 strains, rely on this pathway for the more rapid macrophage uptake they induce compared to other GBS strains. Our findings suggest that this pathway is, indeed, important for macrophage uptake of GBS. Consistent with these findings, we used immunofluorescence microscopy to demonstrate that more virulent strains of GBS induce more actin projections in macrophages than less virulent strains. Additionally, we explored whether PI3K-Akt signaling impacted the ability of GBS to survive within macrophages after phagocytosis and whether this pathway influenced the survival rate of macrophages themselves following GBS infection. The PI3K-Akt pathway was found to promote the survival of both macrophages and intracellular GBS following infection. We also observed that inhibition of the PI3K-Akt pathway significantly reduced GBS-mediated activation of NFκB, which is a key regulator of cell survival and inflammatory responses. Overall, these insights into strain-dependent GBS-mediated manipulation of the PI3K-Akt pathway and its downstream targets in infected macrophages may provide new insights for the development of diagnostic and therapeutic tools to combat severe GBS disease.